Association Between Major Depression and Type 2 Diabetes in Midlife. Issue 5 (June 2015) - Mezuk, Briana; Heh, Victor; Prom-Wormley, Elizabeth; Kendler, Kenneth S.; Pedersen, Nancy L.
ABSTRACT Objective Cohort studies suggest that the relationship between major depression (MD) and Type 2 diabetes (T2DM) is bidirectional. However, this association may be confounded by shared genetic or environmental factors. The objective of this study was to use a twin design to investigate the association between MD and T2DM. Methods Data come from the Screening Across the Lifespan Twin Study, a sample of monozygotic and dizygotic twins 40 years or older sampled from the Swedish Twin Registry (n = 37, 043). MD was assessed by using the Composite International Diagnostic Inventory. Structural equation twin modeling and Cox proportional hazards modeling were used to assess the relationship between MD and T2DM. Results Approximately 19% of respondents had a history of MD and 5% had a history of T2DM. MD was associated with 32% increased likelihood of T2DM (95% confidence interval = 1.00–1.80) among twins aged 40 to 55 years, even after accounting for genetic risk, but was not associated with T2DM among twins older than 55 years. T2DM was associated with 33% increased likelihood of MD (95% confidence interval = 1.02–1.72) among younger, but not older twins. Cholesky decomposition twin modeling indicated that common unique environmental factors contribute to the association between MD and T2DM. Conclusions Environmental factors that are unique to individuals (i.e., not shared within families) but common to both MD and T2DM contribute to their co-occurrence in midlife. However, we cannot exclude the possibility of bidirectional causation as an alternate explanation. It is likely that multiple processes are operating to effect the relation between psychiatric and medical conditions in midlife.